v.2 - Ambedkar, B.R; Jadhav, Narendra(ed.) (New Delhi Konark, 2014)
A follow up to the three-volume set, Ambedkar Speaks, these two volumes present, for the first time, all of Dr Ambedkar's (completed) English writings, in a summary form: Volume I covers all his Political Writings and Volume II his Scholarly Writings (Economics, Sociology, Anthropology and Religion). In addition to his writings, seven landmark speeches especially on Politics and Law and Constitution have also been included for the sake of an all-round understanding of the thought process of Dr Ambedkar.
Volume II: Scholarly writings
Keywords: "Dalits, Dalits- government policy, Political science"